Using the Schlumberger configuration resistivity geoelectric method to estimate the rock structure at landslide zone in Malalak agam. (March 2020) - Permana, R S; Buana, A P; Akmam, A; Amir, H; Putra, A
Abstract: Landslides that often occur in the Malalak sub-district are very detrimental to the community. Landslides in the Malalak sub-district have caused casualties and the closure of the Malalak road segment. According to studies that have been carried out factors that influence the occurrence of landslides are slope, skid field, rock structure and external factors such as rain and earthquake intensity. Rock structures of landslide-prone areas are urgently needed which will be used as reference data to predict potential landslides. This research aimed to estimate the structure of the rock as a reference or supporting data to determine the potential for landslides in the Malalak. The method used in this study is the Schlumberger configuration Resistivity Geoelectric Method. Based on the estimated structure of the rocks in the Malalak region, the rock types in the area consist of Clay, Sandstone, Limestone, Andesite, and Granite.